LncRNA LINC00115 facilitates lung cancer progression through miR‐607/ITGB1 pathway. Issue 1 (13th October 2021) - Wu, Bin; Xue, Xingkui; Lin, Shaoming; Tan, Xing; Shen, Guanle
Abstract: Dysregulated long noncoding RNAs (lncRNAs) have potential roles in various cancer types. The objective of this study was to investigate the expression and the underlying role of long intergenic nonprotein coding RNA 115 (LINC00115) in lung cancer. The relative expression of LINC00115 and miR‐607 in tumor tissues and cells was detected by real‐time PCR. After overexpression or knockdown of LINC00115 expression in tumor cells, the changes in the proliferation, migration, and invasion capacities were detected via Counting Kit‐8 (CCK‐8) assay and transwell assays. The interplay among LINC00115, miR‐607, and integrin β1 (ITGB1) was confirmed by bioinformatics analyses and luciferase reporter assay. In addition, tumor cells with LINC00115 knockdown were injected into nude mice to investigate the effect of LINC00115 on tumorigenesis in vivo. LINC00115 was highly expressed in tumor tissues and cells. LINC00115 promoted the malignant properties of tumor cells. Investigation to its molecular mechanism revealed that LINC00115 functioned as a competitive endogenous RNA (ceRNA), regulating the expression of ITGB1 by sponging miR‐607 to affect tumor growth. The LINC00115/miR‐607/ITGB1 signaling axis might be a novel therapeutic target in lung cancer.